Labor market participation and depression during the COVID-19 pandemic among young adults (18 to 30 years): A nationally representative study in France - Melchior, Maria; Florence, Aline-Marie; Davisse-Paturet, Camille; Falissard, Bruno; Galéra, Cédric; Hazo, Jean-Baptiste; Vuillermoz, Cécile; Warszawski, Josiane; Dione, Fallou; Rouquette, Alexandra (Frontiers in Public Health, 2022)
Objective To examine the relationship between young adults' labor force participation and depression in the context of the COVID-19 pandemic. Design, setting, participants Data come from the nationally-representative EPICOV cohort study set up in France, and were collected in 2020 and 2021 (3 waves of online or telephone interviews: 02/05/2020–12/06/2020; 26/10/2020–14/12/2020; 24/06/2021–09/08/2021) among 2,217 participants aged 18–30 years. Participants with prior mental health disorder (n = 50) were excluded from the statistical analyses. Results Using Generalized Estimating Equation (GEE) models controlled for participants' socio-demographic and health characteristics and weighted to be nationally-representative, we found that compared to young adults who were employed, those who were studying or unemployed were significantly more likely to experience depression assessed using the PHQ-9 (multivariable ORs, respectively: OR: 1.29, 95% CI 1.05–1.60 and OR: 1.50, 1.13–1.99). Stratifying the analyses by age, we observed that unemployment was more strongly associated with depression among participants 25–30 years than among those who were 18–24 years (multivariable ORs, respectively, 1.78, 95% CI 1.17–2.71 and 1.41, 95% CI 0.96–2.09). Being out of the labor force was, to the contrary, more significantly associated with depression among participants 18–24 years (multivariable OR: 1.71, 95% CI 1.04–2.82, vs. 1.00, 95% CI 0.53–1.87 among participants 25–30 years). Stratifying the analyses by sex, we found no significant differences in the relationships between labor market characteristics and depression (compared to participants who were employed, multivariable ORs associated with being a student: men: 1.33, 95% CI 1.01–1.76; women: 1.19, 95% CI 0.85–1.67, multivariable ORs associated with being unemployed: men: 1.60, 95% CI 1.04–2.45; women: 1.47, 95% CI 1.01–2.15). Conclusions and relevance Our study shows that in addition to students, young adults who are unemployed also experience elevated levels of depression in the context of the COVID-19 pandemic. These two groups should be the focus of specific attention in terms of prevention and mental health treatment. Supporting employment could also be a propitious way of reducing the burden of the COVID-19 pandemic on the mental health of young adults.